Multimodal characterization of the responsiveness of eight hepatitis D virus genotype isolates to interferon-alpha treatment - Ding, Yibo; Li, Qiudi; Sha, Yunlu; Si, Ruilin; Feng, Chengqian; Liu, Mei; Feng, Zhanghao; Ding, Xutong; Li, Ying; Fu, Huiyuan; Liang, Shiquan; Yao, Qili; et al. (Journal of virology, 2025)
Chronic hepatitis delta virus (HDV) infection causes the most severe form of viral hepatitis. Although humans produce 12 subtypes of interferon-alpha (IFN-alpha), IFN-alpha 2a has been the only commonly used treatment against HDV. Previously, we characterized eight HDV genotype isolates with varying replication kinetics. Herein, we systematically investigated the antiviral efficacy of IFN-alpha 2a and other IFN-alpha subtypes against HDV genotypes 1-8 during de novo infection, cell mitosis, and in quiescent cells. Our findings revealed that IFN-alpha 2a exhibits potent but varied efficiency against HDV 1-8 isolates upon de novo infection and cell mitosis. Conversely, HDVs in resting cells are resistant to IFN-alpha 2a treatment and the IFN-containing cytokine cocktail collected from peripheral blood mononuclear cells stimulated with TLR7/8 agonist. Mechanistically, both ADAR1 p110 and p150 promote L-HDAg production and inhibit HDV replication. ADAR1 p150, rather than p110, enhances the anti-HDV efficacy of IFN-alpha during de novo infection and cell mitosis, but not in resting cells. Moreover, different subtypes of IFN-alpha exhibit varying anti-HDV activities in both de novo infection and cell mitosis, due to their disparity in activating interferon responses. Among these, IFN-alpha 2a, IFN-alpha 10, and IFN-alpha 14 exhibit the strongest anti-HDV activity and synergize with bulevirtide in suppressing HDV replication. In conclusion, the anti-HDV efficacy of IFN-alpha depends on multiple factors, including HDV genotypes, ADAR1 p150 level, IFN-alpha subtypes, and HDV's different survival strategies. These findings provide valuable implications for the development and optimization of IFN-based therapies.IMPORTANCEChronic hepatitis delta virus (HDV) infection represents the most severe form of viral hepatitis. This study comprehensively evaluated the antiviral efficacy of interferon-alpha (IFN-alpha) subtypes across eight HDV genotypes during de novo infection, cell mitosis, or in quiescent cells. Herein, we found that IFN-alpha exhibits potent but varied efficiency against HDV 1-8 isolates upon de novo infection and cell mitosis. Conversely, HDVs in resting cells are resistant to IFN-alpha subtypes, regardless of the cellular ADAR1 levels. Among different subtypes, IFN-alpha 2a, IFN-alpha 10, and IFN-alpha 14 exhibit the strongest anti-HDV activity and synergize with bulevirtide in suppressing HDV replication. These findings provide crucial insights into the optimization of IFN-based monotherapy and combinational therapy against chronic HDV infection.
Veröffentlicht: 18 September 2025
Gesehen am 28.01.2026